Negotiating morality among women in a Pentecostal church: Perspectives through the materialism, hedonism and egoism cycle - Nyamugama, Sithembinkosi (Cita konsultindo, 2024)
Although materialism, hedonism and egoism have been extensively studied in various contexts including within Christianity, they have largely been treated as concepts which exist in isolation. Where a different conceptual focus has been adopted, it has deployed ubuntu as a uniquely African philosophy and moral concept. Equally incisive is scholarship from St Thomas Aquinas and Pope John Paul II which articulates a Theology of the Body as well as scholarship on the Material Values Scale. The contemporary scholarship helps illuminate the moral complexities that Christian women encounter. In this paper, through the perspectives of women at Apostolic Faith Mission church branch located in Sunnyside, Pretoria, I presented a unified conceptual model to reveal the interconnected nature of moral concepts. The women reveal that materialism, hedonism and egoism are variably connected and justified even in instances where they appear incongruent with normative moral positions. The study therefore intervenes in demonstrating the intricate ways in which morality is perceived and navigated by women in the church. Instead of a straitjacketed conception, morals constitute a dynamic area of Christian life.